Resilience as an element of a sociology of expression - Hempel, Leon,Lorenz, Daniel F. (Enthalten in:Behemoth;Freiburg : Universität, Br. : Univ.-Bibl., 2008-;7, Heft 2, 26-72;Online-Ressource)
Zusammenfassung: Resilience has gained the status of a new leading category for describing societies that increasingly consider themselves faced with crises and thus with uncertainty, vulnerability and susceptibility to failure. Considering the predominant discourse, however, one gets the impression that resilience as a phenomenon of survival under adverse conditions has been displaced into the background. As a mere formula the term is used by a normative, political program of enactment, decreeing resilience in order to exercise control. The phenomenon vanishes the more it is discursively rendered or fixed – whether by science or by politics. This unsatisfactory situation challenges us to ask whether it is possible to theorize resilience from a different viewpoint than that of the current discursive formation together with its critique. The discourse itself may point to a way back to the phenomenon of resilience. Starting with the so-called ‘ecologization of thought‘, resilience is conceptualized as an element of a sociology of expression. Resilience is an emergent phenomenon of individuation and subjectification arising in vibrant assemblages which form these processes and thus resilience itself. While we understand the discourse itself as such an assemblage, we will thus follow resilience in three further constellations – in everyday life, in exceptional circumstances and in protest. However, in all of these contexts resilience is not restricted to human actors, but encompasses all kinds of imaginable ecological, social, technical, and mental entities
10.6094/behemoth.2014.7.2.833
Keywords: Ökologie des Denkens; Resilienz; Soziologie des Ausdrucks; ecology of thought; resilience; sociology of expression; disaster; protest; (local)article; Katastrophe; Protest